An Analysis Code Switching Used By Maudy Ayunda In Program Catatan Najwa Shihab YouTube Video - Arsong, Oktavianus (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2024)
Abstract— This study aims to identify the types of code-switching on Maudy Ayunda in program Catatan Najwa Shihab in YouTube video, and also to identify the reasons why speakers use code-switching in their speech. The research used a descriptive qualitative method. In order to identify the code-switching, this research utilized theories proposed by Appel and Muysken (1987) to classify the types of codeswitching and also the theory proposed by Hoffman (1991) to describe the reasons of codeswitching the end result of this research indicates that all types of code-switching and five reasons for code-switching were found. The end result of this research indicates that all types of code-switching and five reasons for code-switching were found. First, the three types of code-switching were found, namely tag switching, intra-sentential switching, and inter-sentential switching. The most dominant of the types of code-switching occurrence by Maudy Ayunda in programs Catatan Mata Najwa is Intra-Sentential switching with 46 data and Intra-sentential Switching 33 data, meanwhile Tag Switching be the lowest dominant data used by speaker with 7 data. Second five reasons for code switching were found. The most dominant reason is talking about an Intention of Clarifying the Speech Content for the Interlocutor 33 data. Abstract— This study aims to identify the types of code-switching on Maudy Ayunda in program Catatan Najwa Shihab in YouTube video, and also to identify the reasons why speakers use code-switching in their speech. The research used a descriptive qualitative method. In order to identify the code-switching, this research utilized theories proposed by Appel and Muysken (1987) to classify the types of codeswitching and also the theory proposed by Hoffman (1991) to describe the reasons of codeswitching the end result of this research indicates that all types of code-switching and five reasons for code-switching were found. The end result of this research indicates that all types of code-switching and five reasons for code-switching were found. First, the three types of code-switching were found, namely tag switching, intra-sentential switching, and inter-sentential switching. The most dominant of the types of code-switching occurrence by Maudy Ayunda in programs Catatan Mata Najwa is Intra-Sentential switching with 46 data and Intra-sentential Switching 33 data, meanwhile Tag Switching be the lowest dominant data used by speaker with 7 data. Second five reasons for code switching were found. The most dominant reason is talking about an Intention of Clarifying the Speech Content for the Interlocutor 33 data. Abstract— This study aims to identify the types of code-switching on Maudy Ayunda in program Catatan Najwa Shihab in YouTube video, and also to identify the reasons why speakers use code-switching in their speech. The research used a descriptive qualitative method. In order to identify the code-switching, this research utilized theories proposed by Appel and Muysken (1987) to classify the types of codeswitching and also the theory proposed by Hoffman (1991) to describe the reasons of codeswitching the end result of this research indicates that all types of code-switching and five reasons for code-switching were found. The end result of this research indicates that all types of code-switching and five reasons for code-switching were found. First, the three types of code-switching were found, namely tag switching, intra-sentential switching, and inter-sentential switching. The most dominant of the types of code-switching occurrence by Maudy Ayunda in programs Catatan Mata Najwa is Intra-Sentential switching with 46 data and Intra-sentential Switching 33 data, meanwhile Tag Switching be the lowest dominant data used by speaker with 7 data. Second five reasons for code switching were found. The most dominant reason is talking about an Intention of Clarifying the Speech Content for the Interlocutor 33 data.